Therapeutic Levels of Acetaminophen Causing AKI: A Case Report and Literature Review - Hamnah Tayyab; Lavanya Dhondapati; Ashraf Ullah; Mohammed Dheyaa Marsool Marsool; Singh Jagmeet; Khabab Abbasher Hussien Mohamed Ahmed (Clinical Case Reports)
ABSTRACT Our case highlights the importance of being aware of the potential renal complications that can occur with acetaminophen, even when used at dosages slightly above the recommended therapeutic dose.